Remunerative Intercropping Systems for Fall Army Worm Management in Maize - Sivamurugan, A.P.; Pazhanivelan, S.; Suganthi, A. (University of Jaffna, 2023)
Maize (Zea mays L.) is the most promising cereal crop in India after rice and wheat in respect of area and production owing to its wide ecological adaptability. It is grown throughout the year in almost all parts of India with an area and production of more than 8.5 million ha and 20 million tones, respectively. Nevertheless, the productivity of Maize in India is 2345 kg ha-1, which is very low. This is ascribed to frequent occurrence of drought, inadequate soil moisture storage, imbalanced application of manures and fertilizers, widespread occurrence of pest and diseases. Among them, Fall armyworm (FAW),Spodoptera frugiperda, an invasive pest has become a serious threat in influencing the productivity of maize. Hence, a study was conducted during Kharif, 2020 to study the influence of different intercropping systems for FAW management in Maize. The soil was sandy clay loam and low in available N, medium in available P and high in available K with a pH of 8.21.The experiment was laid out in a Randomized Complete Block Design (RCBD) with the following treatments viz., T1 –Maize + Tephrosia,T2 - Maize + Fenugreek, T3 - Maize + Coriander ,T4 - Maize + Marigold, T5 – Maize alone and replicated thrice. A row of C: N hybrid grass was planted in the brim of the field. Based on the results of experimentation, it is concluded that among the intercropping systems in Maize, Maize + Marigold was found to be superior for the management of FAW in Maize which recorded higher Maize equivalent yield (6215 kg ha-1), net return (Rs. 47,181/ha) and BC ratio (1.87).
Keywords: Maize; Intercrops; FAW infestation